Mobbing in the low-wage labor market in Iceland- : a comparison of imigrants and Icelanders - Malgorzata Katrín Molenda 1988- (2016)
Abstract Workplace mobbing has previously been studied to some extent but little research has been made on Icelandic labor market. Findings from former studies have found that mobbing is a serious problem in today’s workplace because it has a highly negative effect on employee life. Negative Acts of Questionnaire-Revised (NAQ-R scale) was used to analyze the frequency of mobbing in Iceland´s low-wage labor market. The purpose of this study was to find out if mobbing is also problem in the Icelandic labor market. Even though the results showed that immigrant employees are not at a higher risk to experience mobbing than Icelandic employees, personal character plays an important role regarding when and how people become targets of mobbing.